Stress at Work: Can the Spiritual Dimension Reduce It? An Approach From the Banking Sector - Robina-Ramírez, Rafael; Medina-Merodio, José Amelio; Estriegana, Rosa; Sánchez-Oro, Marcelo; Castro-Serrano, José (Frontiers in Psychology, 2021)
Stress at work motivated by pressures and labour control can alter the behaviour of workers. Since the 2008 economic crisis, banking in Spain has suffered a series of massive lay-offs to adjust to the new market situation. This new financial restructuring has meant greater labour pressure to achieve the required results. Faced with this adversity, employees have experienced greater stress at work. This work analyses the effect of reinforcing employees’ spiritual dimension to transcend and correctly manage work pressure and stress at work. In so doing, 601 employees from 294 financial entities of five large IBEX banks participated in this pilot project. Through a participatory methodology based on a review of the literature, the study indicators have been delimited. The data obtained have been treated using the SEM-PLS method. The results propose the incorporation of a series of tools to reinforce values and transcendent employee behaviour.